الاقتصاد الصيني ومنهج التدرج في التحول نحو اقتصاد السوق ......سياسات ومؤشرات (المجلة العراقية للعلوم الاقتصادية, 2018)
The Chinese experience is gaining its importance of the major development achievements, after it was of the most backward countries. Therefore, it is useful to go into its case , and keep track of ,its historical and present trends ,particularly in relation to what it followed the path of development associated with varied economic transformation , with the passage of time, beginning of the feudal system , through the applications of socialism and at end the shift towards a market economy and according to gradualism approach, as a last frame for its development path. That was focused on through the analysis of a select set of indicators to evaluate the performance , at the economic , social and environmental levels to determine the suitability of the mentioned approach in the Chinese economic For the purpose of understanding the experience of the transition of china towards a market economy ,according to the same approach, and evaluate the results and reach to the conclusions regarding the validity of the hypothesis, which says the higher performance of china at the economic ,social and environmental levels is a result of the following of the gradual approach to transfer towards a market economy .The study was divided into two major sections .The first one was devoted to track the historical development and the trend of Chinese economic policies , while the second one contains the implication of economic transformation and performance indicators in china